Synthesis, Characterization, Electrochemistry, Catalytic and Biological Activities of Ruthenium(III) Complexes with Tridentate ONO Donar Schiff Base Ligands - Raju, V.V.; Balasubramanian, K.P.; Chinnusamy, V. (Asian Journal of Chemistry, 2010)
New hexa-coordinated ruthenium(III) complexes of the type [RuX(EPh3)2(L)] (E = P or As: X = C1 or Br; L = dibasic tridentate Schiff base derived from the condensation of salicyloyl hydrazide with acetone, ethyl methyl ketone and salicyaldehyde) have been synthesized by the reaction of equimolar amounts of [RuX3(EPh)3] or [RuBr3(PPh3)2(MeOH)] and Schiff base in benzene. The resulting complexes have been charac-terized by analytical, spectral (IR, electronic and EPR), magnetic moment and cyclic voltammetry. An octahedral structure has been tentatively proposed. All the complexes have exhibited catalytic activity for the oxidation of benzyl alcohol, cyclohexanol and cinnamyl alcohol in the presence of N-methylmorpholine- N-oxide as co-oxidant. All the new complexes were found to be active against bacteria such as E. coli, Pseudomonas, Salmonella typhi and Staphylococcus aureus. The activity was compared with standard streptomycin.